Performance Analysis of The Hairpin Heat Exchanger Using Different Nano Fluids (International Journal of Innovative Research in Computer Science & Technology, 2022)
An apparatus that moves heat from one  fluid to another is a heat exchanger. To avoid mixing, the  fluids may be separated by a solid wall, or they may be in  direct touchHairpin Exchangers are available in bare tubes,  finned tubes, U-tubes, straight tubes (with rod-thru  capability), fixed tube sheets, and detachable bundles. They  also come in single tubes (Double Pipe) and numerous tubes  within a hairpin shell (Multitude). The combination  characteristics of nano fluid and base fluid water are  calculated in this article. Magnesium Oxide and silver nano  particle volume fractions of 0.35, 0.45, 0.55, and 0.65  percent at varied velocities (0.5, 1,1.5, and 2 m/s) were used  as nano fluids. The properties of nanofluids are calculated  theoretically, and the results are used as inputs for analysisA  3D model of the hair pin heat exchanger with and without  twisted tape is made using CREO parametric software. CFD  analysis of the hair pin heat exchanger is performed at  different nanofluid volume fractions. The pressure drop,  Reynolds number, heat transfer coefficient, and Nusselt  number are all determined using CFD analysis.
Keywords: Hair pin heat exchanger; CFD study; and finite element analysis